Zrozumieć uczenie się. Skuteczne zdziwienie – wyzwalająca myślenie nauka czytania i pisania w świetle odkryć badań kognitywnych - Kisiel, Weronika (Tomorrow’s school? Tradition and (r)evolutions in education, 2023)
Reading and writing are among the key competences of the modern world, and their development is one of the basic tasks of the school, yet Poland is facing an extremely popular phenomenon of non-reading. Looking for answers to the questions posed in Sense and Nonsense of early childhood education by prof. D. Klus-Stańska, a solution that is unique on a national scale has been developed – Effective astonishment, is learning to read and write that liberates thinking. The latest cognitive research indicates the most important principles that should be met if we want to think about effective learning. The aforementioned concept relates to many of these discoveries, and it is precisely the correlation between this innovative approach and the findings of cognitive research that I demonstrate in the following text. An active student in the learning process, linking with prior knowledge, or activating the emotional and volitional spheres during the acquisition of knowledge make learning effective and attractive.